Penerapan Asas Lex Specialis Derogat Legi Generali pada Kasus KDRT dengan Status Perkawinan Siri - Sutiawati, Sutiawati (Al-Ishlah: Jurnal Ilmiah Hukum, 2023)
This study aims to analyze the application of the principle lex specialis derogat legi generali through Law Number 23 of 2004 in cases of domestic violence with unofficial marriage status. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that Law Number 23 of 2004 effectively applies in cases of domestic violence with unofficial marriage status. An unofficial marriage, even though not registered at the Religious Affairs Office, receives recognition and legal protection under Islamic law provisions. Furthermore, the lex specialis derogat legi generali principle ensures that Law Number 23 of 2004 supersedes the Penal Code in handling domestic violence cases. The Gorontalo District Court Decision Number 323/Pid.Sus/2016/PN Gto has also reinforced this validity, which applied Law Number 23 of 2004 in a case of domestic violence with unofficial marriage status. Conversely, applying the Penal Code in cases of domestic violence with unofficial marriage status would contradict the principle of lex specialis derogat legi generali. Therefore, it is recommended that the Police increase awareness and training on the importance of recognizing unofficial marriage status according to Islamic law in the context of applying Law Number 23 of 2004. For the Public Prosecutor, there needs to be a consistent approach in applying Law Number 23 of 2004 as the foundation for prosecution, ensuring that Law Number 23 of 2004 is prioritized over the Penal Code. Meanwhile, for Judges, it is crucial to continue strengthening jurisprudence that supports the supremacy of Law Number 23 of 2004 in cases of domestic violence with unofficial marriage status, as established in the Gorontalo District Court Decision. It will enhance justice and legal protection for victims in future cases of domestic violence.